A study of hypertensive disorders of pregnancy and the fetal outcome in a tertiary care hospital: a prospective study - Mathapati, Sangamesh S.; Biradar, Aruna M.; Sangolli, Laxmi S.; Mangalwadi, Nidhi A.; S., Gamini B.; S., Sridevi H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pregnancy induced hypertension is one of the major causes of feto maternal morbidity and mortality in pregnancy. The exact cause of PIH is unknown certain factors are known to increase the risk of PIH such as risk factor includes that young women with first pregnancy. Methods: The objective of this study was to assess the socio-demographic and clinico-pathological profile of the patients with hypertensive disorders of pregnancy and its associated fetal outcomes. A prospective study was conducted in department of obstetrics and gynecology Shri B. M. Patil Medical College, Hospital and Research Centre, BLDE (Deemed to be University), Vijayapura Karnataka from 15th July to 15th December 2018. All women admitted to labour ward with diagnosis of hypertensive disorders of pregnancy were included in the study after ruling out the exclusion criteria and thorough history, examination and laboratory evaluation were done and followed till delivery. Results: A total of 123 pregnant women with hypertensive disorder of pregnancy were enrolled in the study. Most of the participants were in the age group of 20 to 30 years. The PIH was seen mostly in primigravida, lower socioeconomic status and with lower educational levels. Emergency LSCS is the most common mode of delivery. Conclusions: The hypertensive disorder in pregnancy affects the majorly younger age group. It is most commonly seen in low socio-economic and uneducated population. Hence, there should be provided with proper antenatal care, early detection of hypertensive disorders for better feto-maternal outcome.